Designing a Web-Based Information System for Scholarship Management: Supporting Access and Rapid Dissemination of Information - Muhammad Shalahuddin Al-Ayyubi Al-Ayyubi; Bachtiar Maulana (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2023)
This abstract presents the design of a web-based information system aimed at enhancing the management of scholarships by facilitating quick access to information and efficient dissemination of relevant updates. Scholarships play a crucial role in providing financial assistance to students and enabling them to pursue quality education. However, the existing manual processes and fragmented information systems often lead to challenges in accessing scholarship details and timely dissemination of information. The proposed system addresses these challenges by leveraging web-based technologies and designing an integrated platform for efficient scholarship management. The system incorporates features such as a centralized database, user-friendly interface, and robust search functionality to enable seamless access to scholarship information. By adopting a web-based approach, the system ensures accessibility from various devices, including desktop computers, laptops, and mobile devices. Moreover, the system emphasizes the importance of fast information dissemination. It enables real-time updates and notifications to keep students, scholarship providers, and other stakeholders informed about application deadlines, eligibility criteria, and any changes in the scholarship programs. Additionally, the system allows for personalized notifications, ensuring that users receive relevant updates based on their preferences and areas of interest. The design of the web-based information system prioritizes security and privacy by implementing stringent authentication mechanisms and encrypted data transmission. It also incorporates features for efficient application submission, document management, and evaluation processes, streamlining the entire scholarship lifecycle. The expected benefits of implementing this system include improved accessibility to scholarship opportunities, reduced administrative overhead, increased transparency in the selection process, and enhanced collaboration among scholarship providers and educational institutions. By leveraging the power of web technologies, the proposed system aims to revolutionize the management of scholarships, ultimately promoting equal educational opportunities and fostering academic excellence.